Bando, banido, abandonado, bandido - Rosa, Miriam Debieux (Percurso, 2018)
Realização: Ana Claudia Patitucci, Bela M. Sister, Célia Klouri, Cristina Parada Franch, Danielle Melanie Breyton, Deborah Joan Cardoso e Silvio Hotimsky